A study on “How Turkish Telecommunication Companies Differentiate Customer Integration Methods for Radical and Incremental Service Innovations” - Mercan, Hikmet Baris (2013)
Innovation is wıdely accepted as a source of sustainable growth and competitive advantage in the literature. In last decades, competition has become more intense due to the new technologies, globalisation of markets and more demanding customers. Hence, being innovative ıs a one of the top priorities for the companies. However, relying solely on the research and development department and company personnel’s ability to innovate in other department has become out-dated. In the innovation literature, it is suggested that companies need to create collaborative relationships with their customers through integrating customers in their product and service innovation development process in order to increase their innovation capabilities by identifying current and future needs of the customers. Even though many studies have been done for customer integration into the companies’ development process, much of the focus is on tangible products. Thus, subject remains limited for the service sector.